2014
DOI: 10.1007/s12013-014-0408-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Effectiveness of Scapulothoracic Joint Control Training Exercises on Shoulder Joint Dysfunction

Abstract: The objective of this study was to examine the clinical effectiveness of scapulothoracic joint control training exercises on shoulder joint dysfunction. Forty patients with traumatic shoulder pain and joint dysfunction were randomized into the treatment or control group. Standard rehabilitation interventions included glenohumeral joint mobilization techniques, ultrasound therapy, traditional Chinese medicine, interference current therapy, and other comprehensive interventions. Patients received scapulothoracic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Conservative treatment, including exercise therapy, is thought to influence various shoulder conditions and outcomes such as pain, restricted range of motion, and functional disability [ 23 , 24 ], but there is considerable uncertainty relating to the relative effectiveness of such approaches on changing scapular position and motion. The results of this systematic review can help clinicians relating to effectiveness of therapeutic exercise on scapular dyskinesis and associated shoulder pain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conservative treatment, including exercise therapy, is thought to influence various shoulder conditions and outcomes such as pain, restricted range of motion, and functional disability [ 23 , 24 ], but there is considerable uncertainty relating to the relative effectiveness of such approaches on changing scapular position and motion. The results of this systematic review can help clinicians relating to effectiveness of therapeutic exercise on scapular dyskinesis and associated shoulder pain.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review by Hanratty et al [ 23 ] showed that physiotherapy exercises are effective in decreasing pain and improving function in patients with subacromial impingement syndrome at short-term follow-up. Scapular muscle exercises are included in the rehabilitation of patients with subacromial impingement syndrome and scapular dyskinesis because the muscular system is one of the major contributors of scapular positioning both at rest and during shoulder movements [ 24 ], but there is considerable uncertainty relating to the relative effectiveness of such approaches on changing scapular position and motion.…”
Section: Introductionmentioning
confidence: 99%
“…The scapula stability training was added to the training of motion range and muscle strength 6 weeks after the operation, and the dynamic closed-chain training could be selected. For instance, the yoga ball stability training could be carried out with the table leaning at an angle of 45°, and the yoga ball was first pushed down to support weight upon 60° anteflexion of both shoulders, and the angle of the treatment table was gradually changed until the anteflexion degree of both shoulders reached 90°, and then the patients could support their weight with only one arm [ 9 ]. The above-mentioned scapula training exercise should be performed once a day or once every other day according to the condition of the patient.…”
Section: Methodsmentioning
confidence: 99%
“…For example, scapular kinematic alterations associated with shoulder impingement, rotator cuff tendinopathy, rotator cuff tears, adhesive capsulitis, and so on, and these patients often reduced serratus anterior and increased upper trapezius activation [8][9][10]. And it was reported that the combination of standard rehabilitation interventions and scapulothoracic joint control training exercises were an effective treatment of the shoulder joint dysfunction [11,12]. Therefore, research on exercises to change scapular muscle activity [13,14] has led to the recognition of the importance of scapular stability for shoulder movement in normal scapular muscle activity.…”
Section: Introductionmentioning
confidence: 99%